Perceived Usefulness, Perceived Ease of Use, Trust, and the Regional Government Information System SIPD - Ni Komang Devi Triyanti; Ni Luh Sari Widhiyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Transparent, accountable, and efficient regional financial management is a key responsibility in ensuring good governance. One of the government’s efforts to realize this is through the implementation of an accounting information system known as the Regional Government Information System SIPD, which plays a critical role in planning, budgeting, and financial reporting within local governments. However, the success of SIPD implementation depends not only on the quality of the system itself, but also on the level of user acceptance and usage. This study aims to examine the influence of perceived usefulness, perceived ease of use, and trust on the acceptance of SIPD use at the Regional Financial and Asset Management Agency BPKAD of Karangasem Regency. The sample was determined using non-probability purposive sampling, with 36 employees who use SIPD as respondents. Data analysis was conducted using multiple linear regression analysis. The results indicate that perceived usefulness, perceived ease of use, and trust have a positive effect on SIPD acceptance. This suggests that when the system is perceived to improve performance, productivity, and effectiveness; simplify tasks; be easy to use, understand, and learn; enhance user skills; be trustworthy; and provide security and protection, user interest, satisfaction, and usage frequency will increase. Theoretically, this study supports the Technology Acceptance Model TAM in explaining the influence of perceived usefulness, perceived ease of use, and trust on SIPD acceptance. Practically, the findings can be used as input and evaluation material for further SIPD development.